Marriage in displacement: Gendered (self)resettlement strategies of Syrian women in Egypt - Dina M. Taha (21797186) (2024)
Drawing on fieldwork data among Syrian refugee women marrying Egyptian men amid forced migration, I explore how displacement reshapes the meaning and purpose of marriage. Many such unions, often customary or polygamous, provoke comparisons to forced marriage and gender‐based violence. Bypassing the reductive exploitation and static narratives, I ask: How does displacement alter refugee women's perceptions of marriage's purpose? And can marriage serve as a strategic tool for (self)resettlement? This investigation urges us to reevaluate the existing range of resettlement options and criteria, offering fresh perspectives on marital strategies post‐displacement. Rather, similar marriages often stem from both affective and practical considerations, challenging colonial dichotomies (e.g., agent/victim) and reinstating the role of factors such as social capital in the trajectories of the uprooted. This study expands understanding of gendered and Othered refugee experiences, highlighting marriage's transformative role in forced displacement and resettlement. It contributes to ongoing discussions on marriage, displacement, and resettlement, urging a nuanced approach that acknowledges the complexities of refugee agency and adaptation. Other Information Published in: The British Journal of Sociology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/1468-4446.13145